Can serum matrix metalloproteinase‐9 and SMAD‐2 levels predict lamina propria invasion in bladder urothelial carcinoma?. Issue 8 (13th May 2021) - Yitgin, Yasin; Erdem, Selcuk; Serilmez, Murat; Duranyıldız, Derya; Verep, Samed; Gasimov, Kamranbay; Tefik, Tzevat; Sanli, Oner; Ozcan, Faruk
Abstract: Introduction: Matrix metalloproteinase‐9 (MMP‐9) has a role in the destruction of lamina propria (LP) of the bladder wall and SMAD‐2 promotes cell‐to‐cell adhesion. This study aimed to investigate the association between LP invasion and serum protein and mRNA expression levels of MMP‐9 and SMAD‐2 in bladder cancer (BC) patients. Methods: Serum samples were taken from 57 patients with suspicious BC before TUR‐BT (Group 1) and 20 patients with benign diseases as control (Group 2). The mRNA expression and serum protein levels of MMP‐9 and SMAD‐2 were analyzed using Real‐Time PCR and ELISA methods, respectively. The comparison of protein and mRNA expression levels of MMP‐9 and SMAD‐2 were done statistically between Group 1 and 2, as well as for different T stages of BC. Results: The protein levels of MMP‐9 (2448 vs 637.5 pg/mL, P  = .0001) and SMAD‐2 (6.85 vs 1.61 P  = .0001) were significantly higher in Group 1 compared to Group 2. The mRNA expression levels of MMP‐9 ( P  = .89) and SMAD‐2 ( P  = .99) did not significantly differ between the groups. The protein levels of MMP‐9 in T1 patients were significantly higher from both of pTa patients ( P  = .018) and pT2 ( P  = .02). The protein levels of SMAD‐2 were not statistically different between T stages. Similarly, the mRNA expression levels of MMP‐9 and SMAD‐2 were not different between T stages. Conclusions: The protein levels of MMP‐9 and SMAD‐2 were increased in BC patients while mRNA expressions were not different. Furthermore, the increased protein level of MMP‐9 in T1 patients was more pronounced which may be related to LP invasion of the tumor.